2021
DOI: 10.3390/v13030422
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Response to the BNT162b2 mRNA COVID-19 Vaccine in Subjects with Prior SARS-CoV-2 Infection

Abstract: Although antibody levels progressively decrease following SARS-CoV-2 infection, the immune memory persists for months. Thus, individuals who naturally contracted SARS-CoV-2 are expected to develop a more rapid and sustained response to COVID-19 vaccines than naïve individuals. In this study, we analyzed the dynamics of the antibody response to the BNT162b2 mRNA COVID-19 vaccine in six healthcare workers who contracted SARS-CoV-2 in March 2020, in comparison to nine control subjects without a previous infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

45
134
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(182 citation statements)
references
References 18 publications
(5 reference statements)
45
134
1
2
Order By: Relevance
“…As has also been reported in a few independent studies 24,25 , we observed comparable and robust IgG responses to spike RBD and NTD in both naïve and previously infected people after full immunization with an mRNA vaccine 24,25 . Previously, we and others have shown that levels of RBD antibodies correlated well to the magnitude of the neutralizing antibodies in symptomatic SARS-CoV-2 infections 19–22,26 .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…As has also been reported in a few independent studies 24,25 , we observed comparable and robust IgG responses to spike RBD and NTD in both naïve and previously infected people after full immunization with an mRNA vaccine 24,25 . Previously, we and others have shown that levels of RBD antibodies correlated well to the magnitude of the neutralizing antibodies in symptomatic SARS-CoV-2 infections 19–22,26 .…”
Section: Discussionsupporting
confidence: 89%
“…Multiple reports have surfaced recently that previously infected individuals may not need or benefit from a second dose of an mRNA vaccine 24,[44][45][46][47][48] . Our data, by contrast, shows that 1/3 rd of previously infected individuals did not produce detectable levels of neutralizing antibodies after the first dose (Figure 3A, Group 1); after the second dose, however, 40% of these non-responders produced neutralizing antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main limitations of this study are represented by the number of subjects included and the short observation time, which does not permit any inference on vaccine efficacy over time. Antibody persistence will be analyzed in ongoing longitudinal studies, which allows the evaluation of the factors affecting magnitude and persistence of the immune response such as previous exposure to SARS-CoV-2 virus [ 27 , 28 ], age and gender [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies conducted in small samples of immunocompetent adults showed higher levels of S-protein IgG after a single jab in individuals with prior COVID-19 than in those without prior COVID-19. 5,23 Our pilot study with 136 residents was the only one to include NH residents. 16 The current study is innovative because it includes a large sample of NH residents and evaluates the effect on antibody response of (i) the time elapsed since COVID-19 infection and vaccination, and (ii) the persistence of a natural immunity against SARS-CoV-2 N-protein at the time of the first vaccination.…”
Section: Discussionmentioning
confidence: 99%